Storage stability and characterization of biochemical, rehydration and colour characteristics of dehydrated sweet corn kernels. (May 2020) - Kumar, Navneet; Kachhadiya, Sagar; Nayi, Pratik
Abstract: The degradation kinetics of dehydrated sweet corn for total sugar, ascorbic acid, TSS, pH, rehydration parameters, colour and moisture content using low density polyethylene pouches (LDPE) and laminated aluminium foil pouches (LAFP) with or without vacuum were studied. The samples were kept for 3 months and were analysed at every 15 days. During the storage, total sugar, ascorbic acid and total soluble solids reduced from 10.50 to 9.73 g/100 g, 9.36 to 8.86 mg/100 g, 83 to 51°Brix respectively. Rehydration coefficient and rehydration ratio reduced from 90.28 to 75.27, 2.64 to 1.56. Colour L∗ value, a∗ value. b∗ value changed from 61.00 to 70.13, 42.93 to 53.27, 55.58 to 64.24 respectively resulting in increase in ΔE value and chroma value up to 16.29, 70.23 to 83.45 respectively. The moisture content increased from 2.12 to 3.92% in packages. The average sensory score of 7.86 even after 90 days of storage in laminated aluminium foil pouch with vacuum indicates that the product may be stored for 90 days satisfactorily. Zero and first order models fitted well and can be used for predicting various properties of dehydrated sweet corn during storage.